Prevalence and incidence of overweight and obesity among Vietnamese preschool children: a longitudinal cohort study - Loan Minh Do (BMC Pediatrics, 2017)
Abstract Background A plateau in childhood overweight and obesity has been reported in some developed countries while in almost all developing countries this problem is on the rise. The aim of this paper is to describe the changes in prevalence of overweight and obesity within a cohort of preschool children followed for 3 years, and to estimate and compare the incidences in urban and rural children of Hanoi, Vietnam. Methods A longitudinal study of a cohort of 2677 children aged 3 to 6 years old at the beginning of the study was conducted in urban DodaLab and rural FilaBavi, Hanoi, Vietnam. Overall, 2602 children, 1311 urban and 1291 rural, were followed for 3 years with identical measurements of weight and height in 2013, 2014 and 2016. Standard methods were used to estimate prevalence and incidence as well as confidence intervals. Results During the three-year follow-up, the overall estimated prevalence of overweight increased from 9.1% to 16.7%. For the urban children, the increase was considerably higher. The overall prevalence of obesity decreased from 6.4% to 4.5% with less decrease in the urban children. In the group of children who were overweight and obese at the start of the study, 41.4% and 30.7%, respectively, remained in the same state three years later. The incidence of overweight and obesity during the three years were 12.4% and 2.7%, respectively. Boys were more likely to develop obesity than girls. Conclusions Already in preschool age, the prevalence of overweight is high and it continues to increase with age, especially in the urban area. Prevention and intervention programs need to start at early preschool age and actions in urban areas deserve priority.